Characteristic signal intensity changes on postmortem magnetic resonance imaging of the brain - Kobayashi, Tomoya; Shiotani, Seiji; Kaga, Kazunori; Saito, Hajime; Saotome, Kousaku; Miyamoto, Katsumi; Kohno, Mototsugu; Kikuchi, Kazunori; Hayakawa, Hideyuki; Homma, Kazuhiro (Japanese Journal of Radiology, 2010)
Purpose We investigated and identified postmortem changes on magnetic resonance imaging (MRI) of the brain to provide accurate diagnostic guidelines. Materials and methods Our subjects were 16 deceased patients (mean age 57 years) who underwent postmortem computed tomography (CT), MRI, and autopsy, the latter of which showed no abnormalities in the brain. The subjects underwent CT and MRI 6–73 h after confirmation of death (mean 26 h), after being kept in cold storage at 4°C. Postmortem MRI of the brain was performed using T1-weighted imaging (T1WI), T2WI, fluid attenuated inversion recovery (FLAIR) imaging, and diffusion weighted imaging (DWI) with parameters identical to those used for living persons. Results In all cases, postmortem CT showed brain edema and swelling. Postmortem MRI showed characteristic common signal intensity (SI) changes, including (1) high SI of the basal ganglia and thalamus on T1WI; (2) suppression of fat SI on T2WI; (3) insufficient SI suppression of cerebrospinal fluid on FLAIR imaging; (4) high SI rims along the cerebral cortices and the ventricular wall on DWI; and (5) an apparent diffusion coefficient decrease to less than half the normal value. Conclusion Postmortem MRI of the brain in all cases showed characteristic common SI changes. Global cerebral ischemia without following reperfusion and low body temperature explain these changes.